Adsorption removal of styrene on C–Cl grafted silica gel adsorbents. (February 2023) - Hou, Shiyu; Huang, Zheng-Hong; Zhu, Tianle; Tang, Yiliang; Sun, Ye; Li, Xiang; Shen, Fangxia
Abstract: The heat desorption of styrene from adsorbents is impracticable owing to its spontaneous polymerization under heating conditions. However, the feature also brings a potential promoting effect on styrene adsorption. Therefore, it is expected to develop the non-regenerative adsorbents with large adsorption capacity by strengthening the polymerization effect. In this work, C–Cl grafted silica gel adsorbents were prepared by introducing (Chloromethyl)dimethylchlorosilane (CMDMCS) and FeCl2 into silica gel. The C–Cl grafted silica gel exhibited excellent styrene adsorption performance, its adsorption amounts for styrene were 4.67 times and 9 times of unmodified silica gel under dry air condition and high humidity condition (RH = 80%), respectively. In addition, the adsorption of styrene on C–Cl grafted silica gel was almost unaffected by the presence of toluene. The characterization of adsorbents after styrene adsorption indicated that the improvement of adsorption capacity of C–Cl grafted silica gel for styrene can be attributed to atom transfer radical polymerization (ATRP) of styrene molecules on modified silica gel during adsorption process. Graphical abstract: Image 1 Highlights: C–Cl grafted SiO2 adsorbents were prepared by introducing CMDMCS and FeCl2 . The adsorption capacity of SiO2 -1.5 for styrene was 4.7 times of SiO2 . The adsorption of styrene on C–Cl grafted SiO2 was almost unaffected by toluene. C–Cl grafted SiO2 showed excellent moisture resistance for styrene adsorption. ATRP occurred during the adsorption process of styrene on C–Cl grafted SiO2 .